Pengembangan LMS “Ngoding.in” dengan model PBL untuk Meningkatkan Hasil Belajar Kognitif Siswa pada Pemrograman Web - Kelvin Dwi Pranata Sembiring; Riza Akhsani Setyo Prayoga (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Learning Management Systems (LMS) support more structured, interactive, and student-centered learning; however, Web Programming instruction still encounters challenges related to fragmented learning materials, separated assignment management, and students’ difficulties in understanding server-side PHP concepts. The ADDIE model was used in this study's Research and Development (R&D) methodology. Students from SMKN 10 Surabaya participated in the study as research subjects. Tests of cognitive learning outcomes, expert validation, interviews, and observations were used to gather data. To ascertain the efficacy of the created LMS, the gathered data was examined utilizing N-Gain analysis, Paired Samples T-Test, Shapiro-Wilk normality testing, and product feasibility assessment. Based on black-box testing, the evaluation results showed that the LMS met all functional requirements and achieved a very feasible categorization. Students' average scores rose from 59.05 on the pre-test to 81.62 on the post-test after implementation. Students' scores before and after utilizing the LMS differed significantly, according to statistical analysis, with a significance value of 0.000 (p < 0.05). Additionally, the N-Gain score of 0.53 was classified as moderate, indicating a significant improvement in cognitive learning outcomes. These results imply that it is possible to include PBL into a Moodle-based LMS for educational purposes and that doing so enhances students' cognitive performance in web programming.